Osteoporosis Related Food Habits and Behaviors: a Cross-Sectional Study among Female Teachers - Lesan Sh; Mirheydari Z; Sotoudeh G; Khajeh Nasiri F; Koohdani F (Tehran University of Medical Sciences, 2010)
Background & Objective: Osteoporosis is a serious metabolic bone disorder and a major health concern in women. Osteoporosis affects the quality of life of women. Studying the osteoporosis related food habits and behaviors can promote health promotion program planning. It seems that female teachers are the best models and educational sources for female students. This study was carried out to determine the osteoporosis related food habits and behaviors among female teachers. Methods & Materials: This study was a cross-sectional study in which 308 female teachers were randomly selected using stratified sampling method from the schools of the 6th district of Tehran. Data were collected using a questionnaire and analyzed using student t-test, one-way analysis of variance and Tukey test. Results: Mean score of osteoporosis related food habits and behaviors was 14.9±4.2 (out of a possible 24 maximum attainable score). Osteoporosis related food habits and behaviors score was significantly higher in the teachers who had higher knowledge score, aged more than 50 years old, had worked for more than 25 years , had used educational books and booklets as the first informational source, and among the post- menopausal teachers (P<0.03). Conclusion: According to the findings, the teachers demonstrated average level of osteoporosis related food habits and behaviors, whereas their mean calcium intake was relatively adequate, but their other food habits and behaviors were relatively inappropriate. It seems developing and implementation of educational programs and offering educational booklets to teacher can help to promote their food habits and behavior which may be helpful in enhancing students' food habits.